Shiga Toxin Subtypes, Serogroups, Phylogroups, RAPD Genotypic Diversity, and Select Virulence Markers of Shiga-Toxigenic Escherichia coli Strains from Goats in Mid-Atlantic US - Eunice Ndegwa; Dahlia O’Brien; Kwame Matthew; Zhenping Wang; Jimin Kim (Microorganisms, 2022)
Understanding Shiga toxin subtypes in E. coli from reservoir hosts may give insight into their significance as human pathogens. The data also serve as an epidemiological tool for source tracking. We characterized Shiga toxin subtypes in 491 goat E. coli isolates (STEC) from the mid-Atlantic US region (stx1 = 278, stx2 = 213, and stx1/stx2 = 95). Their serogroups, phylogroups, M13RAPD genotypes, eae (intimin), and hly (hemolysin) genes were also evaluated. STEC-positive for stx1 harbored Stx1c (79%), stx1a (21%), and stx a/c (4%). Those positive for Stx2 harbored stx2a (55%) and Stx2b (32%), while stx2a/stx2d and stx2a/stx2b were each 2%. Among the 343 STEC that were serogrouped, 46% (n = 158) belonged to O8, 20% (n = 67) to 076, 12% (n = 42) to O91, 5% (n = 17) to O5, and 5% (n = 18) to O26. Less than 5% belonged to O78, O87, O146, and O103. The hly and eae genes were detected in 48% and 14% of STEC, respectively. Most belonged to phylogroup B1 (73%), followed by D (10%), E (8%), A (4%), B2 (4%), and F (1%). M13RAPD genotyping revealed clonality of 091, O5, O87, O103, and O78 but higher diversity in the O8, O76, and O26 serogroups. These results indicate goat STEC belonged to important non-O157 STEC serogroups, were genomically diverse, and harbored Shiga toxin subtypes associated with severe human disease.